Review on Data Mining: Exploring the Applications and Techniques of Data Mining in Various Fields (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Data, information and knowledge are the interesting role of human life. Huge repositories of data with the fast development of technologies have required analyzing and Modeling of big data to predict and analyze the future trends of information. Knowledge discovery in the databases needs methodologies and techniques used into various areas of information systems. Data mining is a knowledge discovery that extracts useful information. It has been a major advance in machine learning, artificial agent systems, and decision making in the expert systems. The last decade, the researcher has surveyed most of the techniques and applications that used in different fields in our life such as manufacturing, education, engineering and business.